The Effectiveness of a Health Education Program Applying Pender’s Health Promotion Model on Self Health-Care Behavioral Modification of Patients with Type 2 Diabetes Mellitus in Sub-District Health Promoting Hospital, Bankha District, Ratchaburi Province - Loykaew, Kwanjai; Vorapongsathorn, Sureepun; Vorapongsathorn, Thavatchai; Chooratna, Kasem (Vajira Medical Journal : Journal of Urban Medicine, 2019)
Objective: To study the effectiveness of a health education program applying Pender’s health promotion model on self health-care behavioral modification of patients with type 2 diabetes mellitus in Sub-District Health Promoting Hospital, Bankha District, Ratchaburi Province. Methods: This study was an experimental design. The sample used in this research was 64 type 2 diabetes patients. They were selected according to the inclusion criteria and were randomly divided into experimental and control groups. Each group consisted of 32 patients. The trial period was 12 weeks. The experimental group received a health education program applying Pender’s health promotion model on self-health care behavioral modification while the control group received the usual health care knowledge from the sub-district health promoting hospital. The questionnaires were used as the instrument in this research to collect the diabetes patient data in 4 times, before, after, and two following trials. The data were analyzed by frequency percentage, mean, standard deviation and repeated measure analysis of variance. Results: The findings showed that 1). The experimental group, after-trial period, obtained higher mean scores in terms of diabetes knowledge, perceived benefits, self-efficacy, activity-related affect, interpersonal and situational influences, commitment to plan of action, and health promotion behaviors higher than those in before-trial period and also higher than the control group with the statistical significant level of p<img title="<" src="https://latex.codecogs.com/gif.latex?<"> 0.05. 2). The mean scores of perceived barriers between the experimental and control groups were not significantly different (p " src="https://latex.codecogs.com/gif.latex?>"> 0.05). 3). The mean change in the levels of fasting blood sugar in the experimental group in after-trial period was significantly lower than that in before-trial. 4). The average level of fasting blood sugar during 4 periods of trials between the experimental and control groups was not statistically different (p " src="https://latex.codecogs.com/gif.latex?>"> 0.05), but interaction effect (number of times of treatment X groups) was statistical significance (p = 0.03). Conclusion: These findings can be used as a guide in planning health-promoting behavior change for the health care of patients with diabetes and other patients with non-communicable chronic diseases.